Novel and advanced MNP molecular markers accurately identify the genetic similarity of Hypsizygus marmoreus strains: a comparative evaluation with ISSR and antagonistic methods - Zhao, Honglei; Wei, Chuanzheng; Zhang, Tuo; Zhao, Yihao; Chen, Xinyue; Lv, Zhiwen; Nie, Menghan; Li, Jian; Liu, Yuanzhen; Xie, Baogui; Liu, Xinrui (Frontiers in Fungal Biology, 2025)
Hypsizygus marmoreus is a wood-rotting fungus of significant medicinal value, extensively cultivated industrially. As the scale of production expands, the issue of “same strains with different names” has become increasingly important, necessitating an accurate, efficient, and rapid method for variety identification. In this study, we resequenced 79 strains of H. marmoreus and selected 32 strains to construct a database comprised of 369 multiple nucleotide polymorphism (MNP) molecular markers and subsequently analyzed the genetic similarity among these strains. The results revealed that none of the 32 selected strains exhibited 100% genetic similarity. Specifically, the genetic similarity of the 369 MNP markers among the white strains ranged from 11.92% to 88.62%, while that of the gray strains ranged from 2.71% to 74.53%, indicating that the gray strains exhibited greater genetic diversity than their white counterparts. Furthermore, we compared the identification results of MNP molecular markers with those obtained from cross-plating experiments and ISSR molecular markers. This comparison highlighted the advantages of the MNP molecular marker method in terms of stability, accuracy, and high efficiency, thereby significantly contributing to the advancement of H. marmoreus strains identification and creation.